HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN DOLLYO CHAGI PADA ATLET TAEKWONDO REMAJA PUTRI BADNUR MEDISA CLUB PEKANBARU - Hanna Rahmalia; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to determine the content of the explosive power of muscle limbs with Dollyo Chagi speed on the athlete Taekwondo adolescent Badnur Medisa Club Pekanbaru. The problem in this research is some athletes Taekwondo adolescent Badnur Medisa Club Pekanbaru which has a kick speed is less good. It exercises its slow strength on the feet when dollyo chagi. The purpose of this study was to determine the power of explosive muscle limb with the speed of kick dollyo chagi. This is a correlational study that aims to determine the relationship between independent and dependent variables. After that, the data normality test with Liliefors stage with significant level of α = 0,05, and the result for normality test of X, L0max ((0,237) <Ltable (0,258), test of normality of variable Y, L0maks (0,155) <Ltable ( 0,258), in other words normal distribution of data, then continued with analysis of product moment generated, if rreult> rtable Has significant influence The results showed: there is a significant relationship between muscle explosive power with kolleo chagi kick speed, rresult ( (0,852)> rtable (0,666) .The conclusion is that there is a significant correlation between the power of leg muscle explosive power with the kick speed of dollyo chagi on Taekwondo athlete adolescent Badnur Medisa Club Pekanbaru.Key Words : Explosive Power of Muscle Limbs, Speed of Dollyo Chagi kick